Comparison of Thin-Film Lithium Niobate, SOH, and POH for Silicon Photonic Modulators - Tai-Cheng Yu; An-Chen Liu; Wei-Ta Huang; Chang-Chin Wu; Chung-Hsun Li; Tsung-Sheng Kao; Shu-Wei Chang; Chin-Wei Sher; Huang-Yu Lin; Chi-Wai Chow; Hao-Chung Kuo (Photonics)
Optical modulators are indispensable components in optical communication systems and must be designed to minimize insertion loss, reduce driving voltage, and enhance linearity. State-of-the-art silicon modulator technology has limitations in terms of power, performance, and spatial size. The addition of materials such as thin-film lithium niobate (TFLN), silicon–organic hybrids (SOH), and plasma–organic hybrids (POH) has improved the modulation performance in silicon photonics. An evaluation of the differences among these modulators and their respective performance characteristics is conducted.